In Vitro Wear Properties of a New CAD/CAM Dental Resin Composite in a Chewing Simulation Test Opposing Itself - Camillo D’Arcangelo; Mirco Vadini; Lorenzo Vanini; Giuseppe Daniele Rondoni; Edoardo Sorrentino; Francesco De Angelis (Applied Sciences)
Wear resistance is of paramount importance for the long-term success of dental materials, especially when they are used for extensive indirect restorations in full-mouth rehabilitations. The present in vitro study aimed to evaluate the two-body wear resistance of a new and recently introduced CAD/CAM resin composite disc (Ena Cad, Micerium S.pA.), to compare it to the wear resistance of other two well-known and already marketed CAD/CAM composites (Brilliant Crios, Coltene/Whaledent AG; Grandio disc, Voco Gmbh) and to a conventional type 3 gold alloy (Aurocast 8, Nobil-Metal). Ten cylindrical specimens (diameter 8 mm, height 6 mm) were manufactured with each material and subjected to a two-body wear test in a dual-axis chewing simulator, performing 120,000 chewing cycles opposing antagonists (2-mm-diameter round tip) made out of the same corresponding materials. The total vertical wear (mm) and the total volumetric loss (mm3) for each sample/antagonist pair were calculated. Representative scanning electron microscope images were also taken. Data were statistically analyzed using one-way analysis of variance tests. No statistically significant differences were recorded among the wear properties of the restorative materials under investigation. The Ena Cad disc showed a wear resistance comparable to the type 3 gold alloy and to the already marketed Brilliant Crios and Grandio disc.